FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Veronica, Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to find out and analyze the influence of Human Capital Efficiency, Capital Employed Efficiency, Structural Capital Efficiency, firm size, and manajerial ownership on firm performance in manufacturing companies listed in Indonesia Stock Exchange from period 2015-2017. The research method used was purposive sampling with a total sample of 64 companies listed on the Indonesia Stock Exchange (IDX). The type of data used is secondary data. Data is obtained from financial statements taken from www.idx.com. The results of the study show that the human capital efficiency, structural capital efficiency, firm size, manajerial ownership do not have a effect on firm performance, while the capital employed efficiency have a positive effect on firm performance.